1997
DOI: 10.1007/s11630-997-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on an axial flow fan stage subjected to circumferential inlet flow distortion and swirl

Abstract: I n v e s t i g a t i o n s on anA x i a l F l o w Fan S t a g e s u b j e c t e d to C i r c u m f e r e n t i a l Inlet F l o w D i s t o r t i o n and Swirl M. G o v a r d h a n K. V i s w a n~t h T h e r m a l T u r b o m a c h i n e s L a b o r a t o r y , D e p a r t m e n t of M e c h a n i c a l E n g i n e e r i n g , I n d i a n I n s t i t u t e of Technology, M a d r a s 600 036, I n d i aThe combined effects of swirl and circumferential inlet flow distortion on the flow field of an axial flow fan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…From the distribution of pressure field on the mid section in Fig. 3, we can see that the location of low pressure is near to the wheel on the side of the outlet, because the air falls away the blades with higher speed [6]. On the other hand, the location of high pressure all lie on the outlet near to the volute tongue because of the backflow at the volute tongue, where the air with high speed impacts the wall.…”
Section: Simulation Results and Analysismentioning
confidence: 95%
“…From the distribution of pressure field on the mid section in Fig. 3, we can see that the location of low pressure is near to the wheel on the side of the outlet, because the air falls away the blades with higher speed [6]. On the other hand, the location of high pressure all lie on the outlet near to the volute tongue because of the backflow at the volute tongue, where the air with high speed impacts the wall.…”
Section: Simulation Results and Analysismentioning
confidence: 95%
“…It can be observed that the circumferential total pressure inlet distortion reduces the overall performance of the rotor to a certain extent. Previous studies 2,3,6,17,18 have indicated that the upstream flow parameters will be redistributed at the rotor inlet due to the interaction between the upstream inlet distortion and the rotor. Figure 9 presents the circumferential distributions of the flow coefficient for two axial locations ahead of the rotor at midspan.…”
Section: Circumferential Total Pressure Distortionmentioning
confidence: 99%
“…Nevertheless, some related numerical and experimental studies have shown that total pressure, total temperature, and swirl distortion sources are related with each other. 2,3,6,17,18 Even the sole total pressure distortion can induce the nonuniformity of inlet airflow direction at the compressor inlet. Hence, it is not enough to link body force source terms with the upstream corrected mass flow.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of swirl and circumferential distortion on the performance of the axial flow compressor was investigated by Govardhan and Viswanath. 15 The study concluded that the pressure rise in the distorted sector was higher than in the undistorted sector. A reduction in the energy coefficient and efficiency was observed under the design point.…”
Section: Introductionmentioning
confidence: 97%